Introgressed Saltol QTL Lines Improves the Salinity Tolerance in Rice at Seedling Stage - Krishnamurthy, S. L.; Pundir, Preeti; Warraich, Arvinder Singh; Rathor, Suman; Lokeshkumar, B. M.; Singh, Nagendra Kumar; Sharma, Parbodh Chander (Frontiers in Plant Science, 2020)
Rice is a staple food crop in Asia and plays a crucial role in the economy of this region. However, production of rice and its cultivating areas are under constant threat of soil salinity. A major QTL, Saltol, responsible for salinity tolerance at seedling stage has been mapped on chromosome 1 using Pokkali/IR29 Recombinant Inbred Lines (RIL) population. The present study was aimed to incorporate Saltol Quantitative Trait Loci (QTL) in two high yielding mega rice varieties i.e. Pusa44 and Sarjoo52 through Marker Assisted Backcross Breeding (MABB). To improve the seedling stage salinity tolerance in these cultivars, we introgressed the Saltol QTL from donor parent FL478 a derivative of Pokkali. A total of three backcrosses (BC3) followed by selfing have led to successful introgression of Saltol QTL. Foreground selection at each breeding cycle was done using micro-satellite markers RM3412 and AP3206 to confirm Saltol QTL. The precise transfer of Saltol region was established using recombinant selection through flanking markers RM493 and G11a. Finally, 10 Saltol near isogenic lines (NILs) of Pusa44 and eight NILs of Sarjoo52 were successfully developed. These NILs (BC3F4) were evaluated for seedling stage salinity under hydroponic system. The NILs PU99, PU176, PU200, PU215, PU229, PU240, PU241, PU244, PU252, PU263 of Pusa44 and SAR17, SAR23, SAR35, SAR39, SAR77, SAR87, SAR123, SAR136 NILs of Sarjoo52 confirmed tolerance to salinity with low salt injury score of 3 or 5. Ratio of Na+/K+ content of Saltol NILs ranged from 1.26 to 1.85 in Pusa44 and 1.08 to 1.69 in Sarjoo52. The successfully developed NILs were further phenotyped stringently for morphological traits to estimate Phenotypic Recovery. Background selection of NILs along with parents was carried out with 50K SNP chip and recovered 94.83–98.38% in Pusa44 NILs and 94.51 to 98.31% in Sarjoo52 NILs of recurrent genome. The present study of MAB has accelerated the development of salt tolerant lines in the genetic background of Pusa44 and Sarjoo52. These NILs could be used for commercial cultivation in saline affected area.